The Incidence rate and risk factors of antenatal stillbirth in Al-Diwaniyah Province at the mid-euphrates region of Iraq: Cross-sectional study - Hayat Jabir AL Sultani; Hasan Osamah Taher AL-Obaidi; Ghufran Jihad Kadhim Shabbani (Journal of Population Therapeutics and Clinical Pharmacology, 2021)
The incidence of stillbirth is variable among different countries but in general ranges from 3.1 to 6.2 per 1000 births. Most of the reported cases of stillbirths come from underdeveloped countries. The adoption of antenatal strategies to care for high-risk women has significantly reduced the incidence of stillbirth in developed countries; therefore, the identification of risk factors associating stillbirth, together with encouraging health facilities to deal with and manage such factors can greatly reduce the incidence of stillbirth in developing countries including ours.To estimate the annual incidence rate of antenatal stillbirth in Al-Diwaniyah province and make an account of the principal risk factors associating with stillbirth in this region of Iraq.The current cross-sectional study was carried out in Al-Diwaniyah Maternity and Children Teaching Hospital at Al-Diwaniyah province, which is a major city of 1,250,000 population and poor socioeconomic state in the mid-Euphrates territory in central Iraq. This included reviewing available birth records for acomplete 1-year period starting from May 1, 2018 to April 30, 2019. Inclusion criteria included fetal death in women who completed 28 weeks of gestation. Fetal death that happened at or after delivery was excluded. The annual incidence rate of stillbirth was approximately 9.8 per 1000 births. Most of the women were from rural areas accounting for 93 (58.1%). The majority of women were either illiterate or completing only primary school, 65 (40.6%) and 73 (45.6%), respectively. Poor socioeconomic status was dominant and accounted for 99 (61.9%). Anemia was seen in a significant proportion of participating women (48.1%). Regular antenatal care was reported in only 3 (1.9%). Cesarean section was seen in significant previous and present deliveries, 58 (36.2%) and 109 (68.1%), respectively. Pregnancy-induced hypertension was seen in 52 (32.5%). Congenital abnormalities were seen in 19 (11.9%) and placental abruption was seen in 31 (19.4%).Conclusions: The annual incidence rate of stillbirth is relatively high in comparison with nearby countries and other regions of the world. Lack of regular antenatal care, poverty, maternal anemia, and pregnancy-induced hypertension appear to be the principal risk factors of antenatal stillbirth in our province.